Non-covalent functionalization of multi-walled carbon nanotubes with cytochrome c: Enhanced direct electron transfer and analytical applications - Eguilaz Rubio, Marcos (2016)
This work reports the non-covalent functionalization (dispersion) of multi-walled carbon nanotubes (MWCNTs) with cytochrome c (Cyt c), the direct electron transfer (DET) after drop-coating deposition of MWCNTs-Cyt c dispersion on glassy carbon electrodes (GCE), and the analytical applications for the highly sensitive quantification of hydrogen peroxide. The dispersion and the resulting modified electrodes were studied by UV-visible spectroscopy, scanning electron microscopy, and electrochemical techniques. The drastic treatment for dispersing the MWCNTs (5.0 min sonication in water with ultrasonic tip) produces a partial denaturation that facilitates the interaction of Cyt c with the CNTs and makes possible an efficient electron transfer between the heme group and the electrode. A critical analysis of the influence of different experimental conditions on the efficiency of the dispersion and on the performance of GCE modified with MWCNTs-Cyt c dispersion is also reported. The analytical parameters obtained with GCE/MWCNTs-Cyt c for the amperometric quantification of hydrogen peroxide at -0.100 V were: sensitivity of (43 ± 1) mA M-1 cm-2, linear range between 1.0 × 10-6 and 1.6 × 10-4 M, detection limit of 1.5 × 10-7 M, reproducibility of 3.1% and repeatability of 3.4%. The biosensor was successfully used for the quantification of hydrogen peroxide in mouthwash and spiked milk samples.